Benchmarking monolayer MoS2 and WS2 field-effect transistors - Sebastian, Amritanand; Pendurthi, Rahul; Choudhury, Tanushree H.; Redwing, Joan M.; Das, Saptarshi (Nature communications, 2021)
Here we benchmark device-to-device variation in field-effect transistors (FETs) based on monolayer MoS 2 and WS 2 films grown using metal-organic chemical vapor deposition process. Our study involves 230 MoS 2 FETs and 160 WS 2 FETs with channel lengths ranging from 5 μm down to 100 nm. We use statistical measures to evaluate key FET performance indicators for benchmarking these two-dimensional (2D) transition metal dichalcogenide (TMD) monolayers against existing literature as well as ultra-thin body Si FETs. Our results show consistent performance of 2D FETs across 1 × 1 cm 2 chips owing to high quality and uniform growth of these TMDs followed by clean transfer onto device substrates. We are able to demonstrate record high carrier mobility of 33 cm 2 V −1 s −1 in WS 2 FETs, which is a 1.5X improvement compared to the best reported in the literature. Our experimental demonstrations confirm the technological viability of 2D FETs in future integrated circuits. Here, the authors perform a benchmark study of field-effect transistors (FETs) based on 2D transition metal dichalcogenides, i.e., 230 MoS 2 and 160 WS 2 FETs, and track device-to-device variations to gauge the technological viability in future integrated circuits.